Changing Patterns of Marriage in Rana-Tharu Communities - Bist, Sita; Bist, Pirt Bahadur (Scholars’ Journal, 2021)
Marriage is an institution of the society which leads to the establishment of family. The Rana-Tharus have their own pattern, culture, rituals, norms, and values regarding marriage. The main aim of the study was to analyse the changing patterns in the Rana-Tharu marriage system. The study employed the situational analysis design of the qualitative research. Semi-structured interview and observation were used as the tools for collecting the data. This study employed the situational analysis design of the qualitative research. Semi-structured interview and observation were used as the tools for collecting the data. For conducting this research, ten informants from Rana Tharu of Shukhalaphanta Municipality-11, Kalwapur villages, Kanchanpur were selected. Thematic analysis was used for the analysis of the data. From the analysed data, it was found that the cultures, rituals, norms that are practised in Rana-Tharu traditional marriage are changed in the present context of marriage. Only those rituals, norms are followed which reflect their cultural identity and some rituals are practised in modified forms. Some of the rituals which seem not so important and are highly costly and time consuming in present context have been abandoned.